Defiant braceros : how migrant workers fought for racial, sexual, and political freedom - Loza, Mireya (David J. Weber series in the new borderlands history., 2016)
"In this book, Mireya Loza sheds new light on the history of the Bracero Program (1942-1964), the binational agreement between the United States and Mexico that allowed hundreds of thousands of male Mexican workers to enter this country on temporary work permits. While this program and the issue of temporary workers has long been politicized on both sides of the border, Loza argues that the prevailing romanticized image of braceros as a family-oriented, productive, legal workforce has obscured the real, diverse experiences of the workers themselves. Focusing on underexplored aspects of workers' lives such as their transnational union organizing efforts, the sexual economies of both gay and straight workers, and the ethno-racial boundaries among Mexican Indigenous braceros, Loza reveals how these men defied perceived political, sexual, and racial norms. Basing her work on an archive of more than 800 oral histories from the United States and Mexico, Loza is the first scholar to carefully differentiate between the experiences of Spanish-speaking guest workers and the many Mixtec, Zapotec, Purhepecha, and Mayan laborers. In doing so, she demonstrates how these transnational workers were able to forge new identities in the face of intense discrimination and exploitation"--